2014
DOI: 10.1038/ncomms6919
|View full text |Cite
|
Sign up to set email alerts
|

Information flow through neural circuits for pheromone orientation

Abstract: Moths use a sophisticated olfactory navigation strategy for resource localization. Here we investigate the neuronal circuits involved in sensory processing to generate locomotor commands for pheromone-source orientation in the moth. We identify a candidate pathway for pheromone processing in the protocerebrum using a mass-staining technique. Our intracellular recordings of pheromone responsiveness detect four major circuits, including a newly identified unstructured neuropil, the superior medial protocerebrum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 70 publications
4
84
0
1
Order By: Relevance
“…As a node of convergence, situated several synapses downstream of sensory neurons and several synapses upstream of motor ganglia, the position and connectivity of the EB-LAL interface implicates it in the translation of sensory representations into motor representations. Experiments in locusts 63 and silk moths 64 identified that LAL modules preserve information about values and saliency associated with selected sensory representations. Our simulations confirm these findings and predict that the EB exerts selection on premotor commands in the LAL by modulespecific columnar projections 10,64 that retain stimulus values by a one-to-one correspondence.…”
Section: Discussionmentioning
confidence: 99%
“…As a node of convergence, situated several synapses downstream of sensory neurons and several synapses upstream of motor ganglia, the position and connectivity of the EB-LAL interface implicates it in the translation of sensory representations into motor representations. Experiments in locusts 63 and silk moths 64 identified that LAL modules preserve information about values and saliency associated with selected sensory representations. Our simulations confirm these findings and predict that the EB exerts selection on premotor commands in the LAL by modulespecific columnar projections 10,64 that retain stimulus values by a one-to-one correspondence.…”
Section: Discussionmentioning
confidence: 99%
“…These moth neurons show so-called flip flop activity that is characterized by sustained periods of alternating high and low firing rates [114]. The transition between the two states is initiated by sensory information, most commonly short pheromone pulses [113], but can also be triggered by light flashes [115]. As neck motor neurons show flip-flop activity as well and head-turns often precede body-turns, the flip flop circuit is considered a control network for turning movements during moth odor plume tracking [116].…”
Section: Steeringmentioning
confidence: 99%
“…In this image projection neurons forming the diffuse lALT bifurcate around the Great Commissure (GC). The ventral aspect of the lALT pathway (v-lALT) proceeds to the lateral protocerebrum with terminals defining the ∆-lateral protocerebral area (∆LP equivalent to the ∆ILPC described in Seki et al 2005;Namiki et al 2014) located anteromedial of the Lateral Horn (LH). The ∆LP consists of parts of the ventrolateral protocerebral neuropils (VLPN: posterior ventral lateral protocerebrum PVLP, posterior lateral protocerebrum, PLP) and superior neuropils (superior lateral protocerebrum, SLP and superior clamp, SCL).…”
Section: Discussionmentioning
confidence: 99%
“…The PN axon followed the v-lALT and made no apparent synaptic contact in the isthmus as it departed the AL before bifurcating in an area of the ventrolateral protocerebral neuropils (VLPN) anteromedial of the lateral horn with one branch invading the posterior ventrolateral protocerebrum (PVLP) (note also the small projection into the anterior ventrolateral protocerebrum, AVLP, arrow) with a second branch projecting more posterio-dorsally close to the posterior lateral fascicle (PLF) and proximal to superior clamp (SC) and superior lateral protocerebrum (SLP). This bifurcated pattern into two main branches that defines the ∆LP region (equivalent to the ∆ILPC region described by Seki et al 2005, andNamiki et al 2014). Note a small amount of staining before the VLPN terminal arbors indicating a small projection into an area populated by d-lALT axons.…”
Section: Figurementioning
confidence: 92%
See 1 more Smart Citation